Diffusion of betamethasone 17-Valerate from palm olein-based vehicle - Win, Thazin; Ahmad, Kausar; Md. Jaffri, Juliana; Edueng, Khadijah (2014)
The current study aims to produce pharmaceutical formulation using palm olein as the oil phase with betamethasone 17-valerate as the active ingredient and to compare efficacy with that of commercial products. Creams were prepared using Span® 20 and Tween® 20 as surfactants, Carbopol® 940 as thickener, methyl paraben, propyl paraben and chlorocresol as preservatives, propylene glycol as solubilizer and distilled water as aqueous phase. The formulations were characterized, subjected to stability studies for 3 months and degradation of betamethasone 17-valerate in the formulations was analysed using HPLC. Evaluation on drug release with three different viscosities was further performed with Hanson Verticle Diffusion Cell System using cellulose acetate and rat skin as membranes and the samples were quantified with HPLC. The results were compared to that of three commmercially available products. The optimized formulation showed particle size ranging from 3 to 14 µm, viscosity 68.2±1.43 mPa.s, yield stress 36.5± 0.2 Pa, thixotropy 647± 58, pH 5.8± 0.1 and zeta potential -51 ± 11 mV. The creams exhibited pseudoplastic behaviour and found to be thixotropic. Less than 5 % of drug is degraded during the 3-month period when subjected to 3 different temperatures. The drug release rates from palm-olein-in-water emulsions were 4.5 times higher than that of commercial products. In conclusion, these findings proved that the creams produced from palm-olein-in-water emulsion could be a superior alternative vehicle for topical drug delivery system.